Determining the Orthotropic Properties of Gerbil Basilar Membrane from Space Constant Measurements. - Liu, Shuangqin.; White, Robert D. (Tufts University. Tisch Library., 2018)
A geometrically nonlinear composite orthotropic plate finite element model is developed to analyze two sets of experimental results in order to extract the two effective elastic moduli, the effective shear modulus and the effective Poisson's ratio for the gerbil cochlea partition. It is shown that the spatial decay rate (the space constant) for the in‐plane deflection is different than for the out‐of‐plane deflection, which has a significant effect on the derived partition properties. Orthotropy ratios (the ratio of the two elastic moduli) are approximately 65 close to the base to 10 in the upper middle turn of the cochlea.